Evaluasi Efisiensi Keuangan: Implementasi Du Pont System - Anggerwati, A. Indah; Jusnia, Jusnia (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
This study examines the financial performance of a company using Du Pont System Analysis. Utilizing a descriptive quantitative approach with secondary data, the research employs various data collection methods. Results reveal suboptimal financial performance over a three-year period, as evidenced by fluctuating and declining Return on Assets (ROA) and Return on Equity (ROE). Both ROA and ROE values fall below industry standards, indicating inefficient asset utilization and management. The analysis highlights the impact of low Total Asset Turnover (TATO) on overall financial performance, suggesting a misalignment between asset growth and income generation. This research demonstrates the effectiveness of Du Pont System Analysis in identifying key areas for financial improvement in business operations.